Development of Social Platforms and New Opportunities in Digital Marketing - Igors Babics; Elita Jermolajeva (Complex Systems Informatics and Modeling Quarterly)
The rapid development of information technology during the last decades has significantly influenced the evolution of digital marketing, changed the methods and models of marketing communications, and promoted the emergence of new digital marketing channels, promotion tools, and communication methods. The article examines the evolution of digital marketing from a historical and technological perspective to build the basis for further research in this area, especially in the context of SMEs in Latvia. Key factors in digital marketing transformation are highlighted: technological innovations, globalization of economic processes, and changes in consumer behavior. Modern information technology innovations are examined, analyzing their possibilities to use new tools in the promotion of product and service brands, developing communication with the target audience, and improving e-commerce methods by introducing artificial intelligence. The article discusses the development of digital marketing, respecting the latest technological innovations, and the concept of Marketing 5.0. The results are reached using content analysis of scientific publications, analytical and statistical reports of European organizations, graphical methods of presenting statistical data, and modeling of trends. The close interdependence of the processes of technological development and the evolution of marketing principles, adapting to changes in consumer behavior with the spread of innovations in wide circles of the public is traced, and modern trends in digital marketing and its tools and technologies are considered.